2007
DOI: 10.1534/genetics.107.072835
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Tor Signaling Requires a Functional Class C Vps Protein Complex in Saccharomyces cerevisiae

Abstract: The Tor kinases regulate responses to nutrients and control cell growth. Unlike most organisms that only contain one Tor protein, Saccharomyces cerevisiae expresses two, Tor1 and Tor2, which are thought to share all of the rapamycin-sensitive functions attributable to Tor signaling. Here we conducted a genetic screen that defined the global TOR1 synthetic fitness or lethal interaction gene network. This screen identified mutations in distinctive functional categories that impaired vacuolar function, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
74
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(82 citation statements)
references
References 60 publications
8
74
0
Order By: Relevance
“…Mutations in genes encoding C-Vps subunits are synthetic lethal with tor1 mutations (note that there are 2 different genes encoding Tor in yeast, and it is Tor1 that is part of Tor complex 1), and C-Vps mutants are hypersensitive to rapamycin, suggesting a role for this complex in Tor complex 1 signaling. 24 It has recently been established that Tor1 activity is decreased to about 30% in C-Vps-mutant yeast cells compared to controls, 25 which exactly matches the reduction of P-S6k levels seen in Vps16A-mutant Drosophila (shown in Fig. 1B).…”
Section: Discussionsupporting
confidence: 75%
“…Mutations in genes encoding C-Vps subunits are synthetic lethal with tor1 mutations (note that there are 2 different genes encoding Tor in yeast, and it is Tor1 that is part of Tor complex 1), and C-Vps mutants are hypersensitive to rapamycin, suggesting a role for this complex in Tor complex 1 signaling. 24 It has recently been established that Tor1 activity is decreased to about 30% in C-Vps-mutant yeast cells compared to controls, 25 which exactly matches the reduction of P-S6k levels seen in Vps16A-mutant Drosophila (shown in Fig. 1B).…”
Section: Discussionsupporting
confidence: 75%
“…The membrane-anchored EGO-GSE complex, found associated with the late endosome and vacuolar membranes, is required for TORC1 localization and activation (Dubouloz et al 2005;Binda et al 2009) and for proper Gap1 trafficking from the endosome to the plasma membrane during amino acid limitation (Gao and Kaiser 2006). Consistent with a link to vacuole function, null alleles of genes encoding class C-VPS components, e.g., PEP3, exhibit synthetic lethality with a tor1D null allele (Zurita-Martinez et al 2007). The presence of glutamate or glutamine suppresses the synthetic lethality of a pep3 tor1 mutant, indicating that nitrogen metabolism and vacuolar function are intimately intertwined.…”
Section: Membrane Transporter Systems and Compartmentalizationmentioning
confidence: 94%
“…Interestingly, a genome-wide synthetic genetic interaction screen revealed that tor1D cells were particularly sick, or not viable, in the absence of individual subunits of either of two protein complexes, namely the EGO complex and the homotypic fusion and vacuole protein sorting (HOPS/ class C-Vps) complex (Zurita-Martinez et al 2007). These and additional genetic data indicated that the class C-Vps/ HOPS complex may, like EGOC, directly or indirectly control TORC1 signalling in response to amino acids.…”
Section: How Is Tor Signalling Regulated?mentioning
confidence: 99%